Redescription of Pseudograpsus intermedius Chhapgar, 1955 (Decapoda, Brachyura, Varunidae) from India - Ng, Ngan Kee; Trivedi, Jigneshkumar; Bhat, Mithila (Zootaxa, 2022)
The identity of Pseudograpsus intermedius Chhapgar, 1955 (Varunidae), a crab species found in mangrove habitats of India is clarified. The re-examination of the holotype male and examination of fresh specimens collected from Goa State, India, revealed that P. intermedius shows significant morphological differences from the generic characters of Pseudograpsus. As such, a new genus Chhapgarus n. gen. is established for the species.